Urgensi Nilai-Nilai Pancasila di Era Globalisasi Saat Ini - Naflah Khalila; Muchlisin Limbong; Dhea Syapira; Wilda Rahmadani; Rizqi Ramadhani; Rizka Cicilia (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Pancasila is the foundation of the Indonesian state, therefore Pancasila is very important in everyday life, and the existence of Pancasila can make the Indonesian nation have guiding principles for recognizing and resolving social, political, legal, cultural and other problems. The values ​​that Pancasila has are good values. Therefore, the values ​​of Pancasila for Indonesian people in their activities are very important, and must be instilled into the souls of every community in Indonesia. In this era of globalization, Pancasila values ​​are starting to fade. This situation can be observed from the emergence of various kinds of problems arising from the non-application of the values ​​of Pancasila, and if they are not immediately addressed, it is possible that the values ​​of Pancasila or the meaning of Pancasila itself will disappear. This research aims to show how important it is to strengthen Pancasila values ​​in the era of globalization, and the method used in this research is the interview method or what is usually called an interview.